An evaluation of major image search engines on various query topics - Çakir, Ece; Bahçeci, Hüseyin; Bitirim, Yıltan (My University, 2008)
This paper investigates the information retrieval effectiveness of major image search engines based on various query topics. Initially, major image search engines, namely, Google, Yahoo, Ask and MSN are selected. Then, seven appropriate topics are determined from the categories of the top search terms used on the web and five queries per topic are chosen. Each query is run on the selected image search engines separately and first forty images retrieved in each retrieval output are classified as being "relevant" or "non-relevant" to calculate precision ratios at various cut-off points for each pair of query and search engine. The results indicated that Google has the best overall retrieval effectiveness in topics "Automotive Manufacturers", "Broadcast Media", "Pharmaceutical and Medical Product" and "Movies" and was followed by MSN in topics "Food and Beverage Brands", "IT and Internet" and Ask in topic "Travel Destinations and Accommodations". All image search engines seem to have the lowest effectiveness for the topic "Food and Beverage Brands". The precision ratio of any one of the image search engines was not the same and changed for every topic. © 2008 IEEE.
3rd International Conference on Internet Monitoring and Protection, ICIMP 2008 --
Keywords: Automotive manufacturers; Broadcast medium; Cut-off; Image search; International conferences; Internet monitoring; Retrieval effectiveness; Search terms; Automobile engines; Automobile parts and equipment; Beverages; Canning; Computer software; Electric breakdown; Engines; Food preservation; Image retrieval; Information retrieval; Information services; Search engines; World Wide Web; Internet